2013
DOI: 10.2337/db13-0039
|View full text |Cite
|
Sign up to set email alerts
|

C-Peptide Activates AMPKα and Prevents ROS-Mediated Mitochondrial Fission and Endothelial Apoptosis in Diabetes

Abstract: Vasculopathy is a major complication of diabetes; however, molecular mechanisms mediating the development of vasculopathy and potential strategies for prevention have not been identified. We have previously reported that C-peptide prevents diabetic vasculopathy by inhibiting reactive oxygen species (ROS)-mediated endothelial apoptosis. To gain further insight into ROS-dependent mechanism of diabetic vasculopathy and its prevention, we studied high glucose–induced cytosolic and mitochondrial ROS production and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
142
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 149 publications
(146 citation statements)
references
References 45 publications
4
142
0
Order By: Relevance
“…Moreover, our previous research demonstrated that AMPK activation played an important role in VNS or ACh ability to protect from mitochondrial biogenesis and antioxidative stress, and provide autophagic cytoprotection during myocardial ischaemia 13, 60, 61. More interestingly, another study demonstrated that AMPK activation prevented mitochondrial fission by decreasing Drp1 and Fis‐1 levels in high glucose‐induced endothelial apoptosis 62. In this study, we showed that VNS treatment activated AMPK and ACC (the substrate of AMPK) in ISO‐induced myocardial damage.…”
Section: Discussionmentioning
confidence: 96%
“…Moreover, our previous research demonstrated that AMPK activation played an important role in VNS or ACh ability to protect from mitochondrial biogenesis and antioxidative stress, and provide autophagic cytoprotection during myocardial ischaemia 13, 60, 61. More interestingly, another study demonstrated that AMPK activation prevented mitochondrial fission by decreasing Drp1 and Fis‐1 levels in high glucose‐induced endothelial apoptosis 62. In this study, we showed that VNS treatment activated AMPK and ACC (the substrate of AMPK) in ISO‐induced myocardial damage.…”
Section: Discussionmentioning
confidence: 96%
“…AMPK also reduces the impact of ROS production on mitochondrial function by avoiding permeability transition pore opening (32) or by promoting mitochondrial biosynthesis through proliferatoractivated receptor-␥ coactivator-1␣. AMPK also inhibits ROSinduced mitochondrial fission and collapse of the mitochondrial membrane potential (7). Finally, AMPK promotes autophagy, minimizing oxidative stress-induced cellular damage by phosphorylating ULK-1 or inhibiting p70S6 kinase phosphorylation (38).…”
Section: Discussionmentioning
confidence: 99%
“…Intracellular ROS generation was determined using 29,79-dichlorodihydrofluorescein diacetate (Molecular Probes, Eugene, OR) staining, as previously described (26). Cells were pretreated with the inhibitors for 30 min and incubated with 10 ng/mL VEGF and 10 mmol/L dichlorodihydrofluorescein diacetate in low-serum media (phenol red-free) for 10 min.…”
Section: Measurement Of Intracellular Ca 2+ Levels and Ros Generationmentioning
confidence: 99%